The choice of renal replacement therapy in patients with a delayed renal graft function in the early postoperative period - E. I. Pervakova; I. V. Alexandrova; A. G. Balkarov (Трансплантология (Москва))
The treatment outcome of 78 renal transplant recipients with a delayed graft function has been reviewed that accounts for 35.3 % of all operated patients. In the early postoperative period, 41 of them received a continuous venovenous hemodiafiltration, and 37 received a standard hemodialysis.A continuous venovenous hemodiafiltration in the initial 24 hours after surgery appeared to make a more pronounced corrective effect on the renal graft function recovery. A later initiation of renal replacement therapy (RRT) was associated with a significantly longer oligoanuria period, and also with an increased incidence of acute rejection in the patients who received a standard hemodialysis.